(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
In this article, the author addresses aspects of a Poetics of the Simple applied to the practice of the Lambe-Lambe Theater. Going through essential themes to the development of the aforementioned scenic language in terms of its encounter with creative partnerships and the public, such as action through gaps, humility, singularity, simplicity and sincerity, reflecting on the process of dissemination of the Lambe-Lambe Theater in the world.